2010
DOI: 10.4014/jmb.1007.07009
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Production of an Inulinase in a Saccharomyces cerevisiae gal80 Strain

Abstract: The inulinase gene (INU1) from Kluyveromyces marxianus NCYC2887 was overexpressed by using the GAL10 promotor in a ∆gal80 strain of Saccharomyces cerevisiae. The inulinase gene lacking the original signal sequence was fused in-frame to a mating factor α signal sequence for secretory expression. Use of the ∆gal80 strain allowed for the galactose-free induction of inulinase expression using a glucose-only medium. Shake-flask cultivation in YPD medium produced 34.6 U/ml of the recombinant inulinase, which was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…It has been found that the engineered strains of S. cerevisiae carrying the exo-inulinase gene show a higher inulinase activity than those carrying the endo-inulinase gene. For example, the exo-inulinase gene from K. marxianus NCYC2887 was overexpressed by using the GAL10 promoter in a S. cerevisiae △gal80 strain, and the recombinant inulinase activity was 34.6 U/mL (Lim et al 2010). Moreover, our recent results have indicated that after INU1 from M. guilliermondii strain 1 was actively expressed in Saccharomyces sp.…”
Section: Discussionmentioning
confidence: 97%
“…It has been found that the engineered strains of S. cerevisiae carrying the exo-inulinase gene show a higher inulinase activity than those carrying the endo-inulinase gene. For example, the exo-inulinase gene from K. marxianus NCYC2887 was overexpressed by using the GAL10 promoter in a S. cerevisiae △gal80 strain, and the recombinant inulinase activity was 34.6 U/mL (Lim et al 2010). Moreover, our recent results have indicated that after INU1 from M. guilliermondii strain 1 was actively expressed in Saccharomyces sp.…”
Section: Discussionmentioning
confidence: 97%
“…Engineering S. cerevisiae strains with heterologous inulinase genes to enhance inulinase production has been explored by plasmid transformation . However, selective pressure is required for recombinants generated by this strategy, which is not practical for industrial application.…”
Section: Discussionmentioning
confidence: 99%
“…KmINU production using K. marxianus ATCC 16045 under various culture conditions has been tested, and a maximal yield of 208 U/ml has been achieved [24]. To improve inulinase production, heterologous expression systems have been tested [10][11][12][25][26][27][28]. However, the specific activities and production titres of those products remained low (Table 2), which could be a major obstacle for the large-scale production and use of inulinase.…”
Section: Discussionmentioning
confidence: 99%